2003
DOI: 10.1007/s00359-003-0429-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and autoradiographical characterization of serotonin transporter-like activity in sporocysts of the human blood fluke, Schistosoma mansoni

Abstract: The present study focuses on the role of the biogenic monoamine serotonin (5-hydroxytryptamine) in the biology of sporocyst stages of the human blood fluke, Schistosoma mansoni, and its importance during obligate development within its snail host Biomphalaria glabrata. Based on previous work demonstrating that snails infected with S. mansoni have reduced levels of 5-hydroxytryptamine, we hypothesized that sporocysts actively transport this molecule from the host milieu. Intact sporocysts isolated in vitro take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Several reports have described a serotonin transporter-like activity in adult worms and sporocysts in the human parasite Schistosoma mansoni (Bennett and Bueding, 1973; Wood and Mansour, 1986; Boyle et al, 2003). The serotonin transporter (SERT) has been cloned from several mammalian species (Mortensen et al, 1999) and also from the nematode Caenorabditis elegans (Ranganathan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have described a serotonin transporter-like activity in adult worms and sporocysts in the human parasite Schistosoma mansoni (Bennett and Bueding, 1973; Wood and Mansour, 1986; Boyle et al, 2003). The serotonin transporter (SERT) has been cloned from several mammalian species (Mortensen et al, 1999) and also from the nematode Caenorabditis elegans (Ranganathan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in S. mansoni have demonstrated that citalopram and clomipramine function as selective serotonin reuptake inhibitors by inhibiting the S. mansoni 5-HT serotonin transporter SmSERT in a heterologous expression system (Patocka and Ribeiro, 2007; Fontana et al, 2009). Although Boyle et al (2003) did not detect serotonin transporter activity in miracidia they were only examining the uptake of exogenous 5-HT and would have likely missed endogenous 5-HT transport. Consistent with our finding that the treatment of miracidia with citalopram results in increased cAMP, serotonin receptors in S. mansoni have been shown to function as G-stimulatory proteins in the cercariae, schistosomula and adult stages (Kasschau and Mansour 1982a; Kasschau and Mansour 1982b).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this transport is unclear, given that the parasite also synthesizes the amine endogenously. It has been suggested that endogenous biosynthesis may be downregulated in the parasitic stages and that exogenous transport is needed to supplement internal production (Hamdan and Ribeiro 1999;Boyle et al 2003). Alternatively, the transport system may be used to sequester excess exogenous serotonin that permeates the tegument and might otherwise be harmful to the parasite.…”
Section: Bas In Schistosomes: Neuronal Localization Biosynthesis Andmentioning
confidence: 98%
“…Schistosomes can take up exogenously supplied serotonin in vitro via a dosedependent, saturable mechanism (Catto and Ottensen 1979;Boyle et al 2003). This has been reported in both adult worms and parasitic larval stages, particularly the snail stages, where the intake of exogenous serotonin is sufficiently high to deplete circulating serotonin levels in the host (Manger et al 1996;Boyle et al 2003). The significance of this transport is unclear, given that the parasite also synthesizes the amine endogenously.…”
Section: Bas In Schistosomes: Neuronal Localization Biosynthesis Andmentioning
confidence: 99%